Exploring the Profile of Numerical Resilience in Elementary Pre-Service Teachers: A Portrait of Readiness to Face Challenges of the 21st Century - Rakhmawati, Yeni; Murti, Rahayu Condro (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
In this era of disruption, recilience of numeracy plays a role as one of the skills used to compete in the global world. The urgency of resilience is as a mental guideline to fight in various challenges. Numerical resilience also plays a role as a way for teachers to adapt to various very rapid rates of change. This study aims to analyze the numeracy resilience profile of prospective elementary school teacher education teachers in Yogyakarta. The method used is quantitative descriptive with data collection through tests, observations, and interviews with 159 students. Data analysis uses statistical descriptive to describe the condition of numeracy resilience, including perseverance, self-confidence, ability to socialize, self-motivation, use of ICT, and creativity in producing innovative solutions. The results of the study indicate that the level of numeracy resilience of prospective teachers is still limited, with an average score indicating mental resilience that needs to be improved. Students tend to be less active in socializing and dialogue and building motivation from failure. The use of ICT and various learning resources is also still limited. In addition, the ideas and innovative solutions produced by prospective teachers are still lacking, indicating the need to strengthen creativity and problem-solving skills. These findings indicate the need for more intensive educational interventions to prepare prospective teachers to face the challenges of 21st century education. Efforts needed include in-depth training on the use of ICT, improving social skills, and strengthening critical and creative thinking skills in designing numeracy learning in elementary schools.